Consumo de nutrientes, comportamento ingestivo, características de carcaça e de componetes não-carcaça de ovinos Santa Ines alimentados com diferentes níveis energéticos - Fontenele, Rildson Melo (2010)
The objective of this study to evaluate nutrient intake, feeding behavior, daily weight gain (DWG), feed conversion (FC), feed efficiency (FE), carcass characteristics, commercial cuts categories of retail cuts, weight internal organs, and compartments gastrointestinal contents, weight and yield of the edible offal and panful of lamb on the growing, fed different levels of metabolizable energy (ME). We used 20 animals lamb, non-castrated, with average weight of 13 ± 0.56 kg and average age of 50 days, which were distributed in four treatments with different energy levels (2.08, 2.28; 2.47 and 2.69 Mcal/kg DM) in a randomized block design with five replications. The Tifton 85 hay was used as roughage. When animals of each treatment reached the average weight of 28 kg, were slaughtered and weights of carcass characteristics and retail cuts as well as the organs and viscera were registered compared with the same parameters of control animals (fed with 2,08 Mcal/kg DM - lower energy level). Regression equations were adjusted to determine the effect of the level of ME treatments on the weights of each organ and viscera. Was detected linear effect of increasing levels of energy (P<0.05) on dry matter intake, organic matter, crude protein, fat, carbohydrates, no fiber and total digestible nutrients, expressed as g/day. NDF intake (%BW g/w 0,75 ) decreased linearly (P<0.05) with increasing energy levels in diets due to the reduction in NDF content in total dry matter of rations. The times of feeding and chewing total, expressed in h/day, decreased (P<0.05) with the energy levels of experimental diets, but the idle time increased linearly (P<0.05), while the time rumination was not affected (P>0.05). The variables: number of ruminal bolus, chewing number, number of chews per bolus rumen and chewing time per bolus rumen were not affected (P>0.05) by levels of energy in the rations. Effect was observed linear increase (P<0.05) in nutritional plan for DWG, with values of 86.60, 120.14, 142.19 and 161.76 g/day for the levels of 2.08, 2.28, 2.47 and 2.69 Mcal/kg DM, respectively. Reported a significant effect of diet on the FC and FE. The loss in fast, true yield, hot carcass and cold, as well as loss in cooling, expressed in kg and percentage, were not affected (P>0.05) by energy rations. As for hot carcass xii weight and cold and the empty body weight in kg, there was increased linearly (P<0.05) as it increased the levels of metabolizable energy in experimental diets. Influence the energy levels for the rib and shoulder (P<0.05). For the cuts of the first category, expressed in kilograms and percentage, and third category, expressed in percentage only is found through regression analysis, the energy levels in diets did not influence (P>0.05) the weight of these cuts. But the cut of second category, expressed in kg and percentage was influenced (P<0.05) by levels of energy in the rations. There was no effect (P>0.05) of metabolizable energy levels on the weights of the heart and lungs, expressed in kilograms and percentage, as well as the weight of the contents of the gastrointestinal tract (P>0.05), expressed in kg and percentage. Linearly increased (P<0.05) for weights in kilograms and percentage of liver. Was detected, linear and quadratic increases (P<0.05) for weights in kg and percentage, kidneys and spleen. However, there was no influence (P>0.05) of the energy levels of experimental diets on weight in kg of rumen-reticulum and omasum as well as to the abomasum, kg and percentage, and the small intestine, expressed percentage. As for the weight of rumenreticulum and omasum, in percentage, we observed a linear decrease (P<0.05) with increasing levels of ME. The weight of the small intestine in kg, was positively influenced (P<0.05) as a function of levels of the experimental diets. As for the weights in kilograms and percentage of the large intestine, there was a linear increase and quadratic (P<0.05), respectively, as they increased the levels of ME in experimental diets. In this study, no significant effect (P<0.05) for weights in kg and percentage fats, perirenal, mesenteric and heart. Increased levels of energy significantly (P<0.05) weight of the edible offal, which increased with increased levels of concentrate. However, there was a quadratic effect (P<0.05) on yield and its derivation is set to a point of maximum level of 2.69 Mcal/kg DM, which remained the best return. The energy levels had significant effects, also (P<0.05) over the panful weight and yield expressed in kg and percent, respectively. The increase in the levels of metabolizable energy of diets influences the nutrient intake and ingestive behavior, improves feed conversion, feed efficiency and maximize weight gain, weight cuts the second category, in percentage and kilograms, and the third category, kg, as well as internal organ weight and the weight and yield of the edible offal and panful of lamb growth